Recent progress in pharmaceutical excipients as P-glycoprotein inhibitors for potential improvement of oral drug bioavailability: A comprehensive overview - Fitrianti Darusman; Taofik Rusdiana; Iyan Sopyan; Hanifa Rahma; Millati Hanifa (Pharmacia)
Pharmaceutical excipients such as P-glycoprotein inhibitors can also increase the solubility and affinity of drugs to the intestinal membrane, enhance paracellular pathways and endocyte uptake, and activate lymph transport pathways, thereby increasing the bioavailability of oral drugs. This review aims to review and assess the performance of pharmaceutical excipients as P-glycoprotein permeability inhibitors in improving oral drug bioavailability in drug formulations by evaluating meta data from P-glycoprotein efflux in permeability and pharmacokinetics studies. The review results are pharmaceutical excipients that have proven effective as P-glycoprotein inhibitors from the surfactant and polymer groups, namely TPGS and Poloxamer 188, respectively. All nanosystems incorporating pharmaceutical excipients as P-gp inhibitors show potential in enhancing the permeability and bioavailability of oral drugs when compared to conventional formulations. The effectiveness of these systems has been evaluated through in vitro (Caco-2 cells), ex vivo (everted gut sac), in situ (SPIP), and in vivo (AUC) methods.